PRINCIPLES OF ANALYSIS OF WATER-GRAVITY PROCESSES AND THEIR INFLUENCE ON FUNCTIONING OF NATURE-TECHNOGENIC SYSTEMS IN CARPATHIAN REGION - IVANIK, O.; LISOVA, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
The main approaches to the study of water-gravity processes in Carpathian region have been determined. They are lied in research of strain-deformed state of geological environment. The main factors of landslide formation have been analyzed. The parameters whish must analyzed in water-gravity processes analytical modul have been estimated.